Prolonged Delivery of Ciprofloxacin and Diclofenac Sodium from a Polymeric Fibre Device for the Treatment of Peridontal Disease. (14th November 2013) - Johnston, Deanne; Choonara, Yahya E.; Kumar, Pradeep; du Toit, Lisa C.; van Vuuren, Sandy; Pillay, Viness
Abstract : In vitro analysis of drug release and antimicrobial activity of the coblended crosslinked polymeric fibre device (PFD) were investigated. The fibre loaded with ciprofloxacin and diclofenac sodium was comprised of alginate and glycerol crosslinked with barium cations. The pH dependent drug release was evident with ciprofloxacin and diclofenac sodium diffusing from the fibre at pH 4.0 compared to pH 6.8, where the fibre swelled and eroded resulting in zero-order drug release. Agar diffusion studies followed by minimum inhibitory assays were conducted to determine the antimicrobial activity of the device against Escherichia coli, Enterococcus faecalis, and Streptococcus mutans . The antimicrobial activity of the PFD was confirmed in both test assays against all test pathogens. The MIC ranges at pH 4.0 for E. coli, E. faecalis, and S. mutans were 0.5–0.8, 0.4–1.1, and 0.7–2.1 μ g/mL, respectively. At pH 6.8, similar efficacies (0.3–0.5 μ g/mL for E. coli and E. faecalis and 0.6–1.0 μ g/mL for S. mutans ) were observed. The effect of varying the plasticizer and crosslinking ion concentration on drug release profile of the fibers was further elucidated and conceptualized using molecular mechanics energy relationships (MMER) and by exploring the spatial disposition of geometrically minimized molecular conformations.